Challenges of Plateau State Polytechnic English Lecturers in Utilizing ICT for Manpower Development - Innocent Nasuk Dajang; Mandong Mathias Ayuba; Samuel Mahanan (PT Publikasiku Academic Solution, 2023)
Information Communication Technology (ICT) facilitates teaching and learning especially in the 21st century where online/digital resources have taken over the globe. The polytechnic is designed to train students who form the nation’s manpower. This paper examined the challenges faced by Plateau State Polytechnic English lecturers in utilizing ICT for manpower development. The study was necessitated by the call from educators around the world for the incorporation and effective utilization of online resources in teaching and learning. In order to investigate the challenges experienced by lecturers in the polytechnic over the utilization of ICT in manpower development through the teaching of English, a Focus Group Discussion (FGD) was conducted on the departmental WhatsApp platform of the Department of General Studies of the polytechnic consisting of eighteen English lecturers. The study adopted Computer-Aided Language Learning (CALL) as its framework. The result of the FCD revealed among others that there were so many problems hampering the utilization of ICT in the teaching and learning in the institution. These challenges principally are related to data infrastructure, knowledge infrastructure and management infrastructure. The study concluded that there was need to put in place ICT facilities in the polytechnic for the lecturers to utilize in the teaching of English being the central language of communication in the development of the nation’s manpower. Key words: Challenges, ICT, Manpower, Polytechnic, Utilization.